Cultural differences in the efficacy of unexpected questions, sketching, and timeline methods in eliciting cues to deception - Tache, Irina; Warmelink, Lara; Taylor, Paul; Hope, Lorraine (Frontiers in Psychology, 2023)
Asking unexpected questions, asking the interviewee to sketch the room, and asking the interviewee to make a timeline are techniques that have been shown to help an interviewer detect deceit. However, evidence on the efficacy of these techniques comes from studies of North America and North-West European participants, who are on average more individualistic (i.e. value individual achievements and uniqueness over group achievements) than people from other parts of the world. In two experiments involving participants with individualistic and collectivistic cultural backgrounds, we provide a more culturally diverse test of these techniques. Specifically, this paper describes two experiments that investigated these interviewing techniques in people who are recent migrants to the UK. Experiment 1 used the LIWC categories “I”, “we”, “cognitive processes” and “social processes” as the dependent variables; Experiment 2 measured details provided in a sketch and a timeline. The results show no effects of veracity in either of these experiments, although various effects of cultural differences on the outcome variables were observed. This suggests that cues to deception may not necessarily generalise to people from different cultural backgrounds. These results highlight the importance of conducting lie detection research across different countries and cultures.